Hereditary stomatocytosis vs elliptocytosis presenting recurrent pancreatitis - Ingle, Achala Arvind; Gupta, Ishank; Bhattacharya, Meenakshi (International Journal of Research in Medical Sciences, 2024)
Hereditary stomatocytosis is a rare autosomal dominant genetic disorder due to an abnormality of red cell permeability to monovalent cations resulting in alteration in water content of red cells. Hereditary elliptocytosis is autosomal dominant disorder caused by inherited mutations in genes encoding red cell membrane. Patient may show up with symptoms of varying severity. We present a case of 35-year-old male with recurrent episodes of abdominal pain, yellowish discolouration of eyes and skin, nausea and vomiting since 2015. He was treated symptomatically earlier but cause was still obscured. Patient underwent liver biopsy and multiple blood examinations but etiology was still not determined. In 2024 patient was again diagnosed with acute pancreatitis and acute kidney injury, evaluated for hyperbilirubinemia and MRCP was suggestive of cholelithiasis without cholecystitis. With a suspicion of hemolytic anemia, peripheral smear of the patient was done which revealed stomatocytosis vs elliptocytosis. Meanwhile Patient was stabilized and referred for genetic testing.